Determinants of Emotional Beliefs about Shared Values in Organizations - Galih Panjalu Pramono; Dyah Purwaningrum; Sutaat Sutaat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the impact of competency development on affective commitment mediated by career development. The population in this study were all teachers at a junior high school in Banyumanik, Semarang, totaling 52 people, with a sample of all members of the population. The analysis tool uses regression and sobel analysis. The results of the study found that competency development has a positive effect on career development, career development has a positive effect on affective commitment. competency development has a positive effect on affective commitment. career development is able to mediate the effect of competency development on affective commitment